Interfacial precipitation of phosphate on hematite and goethite - Wang, L.; Putnis, Christine; Hövelmann, J.; Putnis, Andrew (M D P I AG, 2018)
© 2018 by the author. Licensee MDPI, Basel, Switzerland. Adsorption and subsequent precipitation of dissolved phosphates on iron oxides, such as hematite and goethite, is of considerable importance in predicting the bioavailability of phosphates. We used in situ atomic force microscopy (AFM) to image the kinetic processes of phosphate-bearing solutions interacting with hematite or goethite surfaces. The nucleation of nanoparticles (1.0-4.0 nm in height) of iron phosphate (Fe(III)-P) phases, possibly an amorphous phase at the initial stages, was observed during the dissolution of both hematite and goethite at the earliest crystallization stages. This was followed by a subsequent aggregation stage where larger particles and layered precipitates are formed under different pH values, ionic strengths, and organic additives. Kinetic analysis of the surface nucleation of Fe-P phases in 50 mM NH4H2PO4at pH 4.5 showed the nucleation rate was greater on goethite than hematite. Enhanced goethite and hematite dissolution in the presence of 10 mM AlCl3resulted in a rapid increase in Fe-P nucleation rates. A low concentration of citrate promoted the nucleation, whereas nucleation was inhibited at higher concentrations of citrate. By modeling using PHREEQC, calculated saturation indices (SI) showed that the three Fe(III)-P phases of cacoxenite, tinticite, and strengite may be supersaturated in the reacted solutions. Cacoxenite is predicted to be more thermodynamically favorable in all the phosphate solutions if equilibrium is reached with respect to hematite or goethite, although possibly only amorphous precipitates were observed at the earliest stages. These direct observations at the nanoscale may improve our understanding of phosphate immobilization in iron oxide-rich acid soils.